Effects of sulphuric acid concentrations during solvolysis process of carbon fiber reinforced epoxy composite - Muhammad Falaq Muhammad Faisal,; Azman Hassan,; Khong, Wui Gan; Mohd Nazrul Roslan,; Azrin Hani Abdul Rashid, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Developing a cost-effective technique of reclaiming carbon fibers without significantly deteriorating their quality has gained much importance. This paper reports on reclaiming carbon fibers from the carbon fiber reinforced polymer (CFRP) by solvolysis technique using sulphuric acid. The main objective of this work was to determine the lowest sulphuric acid concentration which can remove the epoxy resin from the composites, at room temperature and atmospheric pressure. The sulphuric acid concentrations used ranged from 11 to 18 mol L-1 with 30 min reaction time and 50 mL volume. Thermogravimetric analysis (TGA) showed that the fiber content of the composites is 68% by weight. From the solvolysis process, mass of decomposed epoxy resin decreased with decreasing acid concentrations. SEM images show that the residual epoxy adhering to the fibers after solvolysis increased with decreasing molarity. Acid concentrations lower than 15 M were found to be not effective in removing the epoxy resin from the carbon fibers. The tensile strength and Young’s modulus of all the reclaimed fibers is marginally lower than the untreated carbon fibers. The tensile strength was found to increase as the acid concentration decreases with fibers in 15 M acid showed the highest tensile strength of 3.43 GPa (99.1% strength retention). Similar trend was also observed for Young’s modulus. The study shows the potential of sulphuric acid to reclaim carbon fiber from the CFRP with 15 M giving the optimum properties in terms of tensile properties retention and epoxy resin decomposition.